2017
DOI: 10.1128/aem.02840-16
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation on Stainless Steel by Streptococcus thermophilus UC8547 in Milk Environments Is Mediated by the Proteinase PrtS

Abstract: In Streptococcus thermophilus, gene transfer events and loss of ancestral traits over the years contribute to its high level of adaptation to milk environments. Biofilm formation capacity, a phenotype that is lost in the majority of strains, plays a role in persistence in dairy environments, such as milk pasteurization and cheese manufacturing plants. To investigate this property, we have studied S. thermophilus UC8547, a fast-acidifying dairy starter culture selected for its high capacity to form biofilm on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…The results obtained clearly showed that the strain carrying the prophage had a significantly higher adhesion phenotype, compared to the A33 phage-cured strain (Table 2 ), thus highlighting that in S. thermophilus , likewise in L. lactis , the cell wall integrity is correlated with biofilm formation. More recently, S. thermophilus biofilm formation was correlated to the presence of the cell-wall protease PrtS which was demonstrated to trigger an aggregative phenotype ( Bassi et al, 2017 ), but this cannot be the case of strain DSM20617 T because it is protease-negative ( Arioli et al, 2007 ). In addition, to investigate the role of phage lysin in the S. thermophilus chain length, we evaluated the differential sedimentation rates of bacteria according to their chain-forming ability and/or cell size in semi-liquid medium (i.e., liquid M17 – lactose medium containing 0.15% wt/vol agarose).…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained clearly showed that the strain carrying the prophage had a significantly higher adhesion phenotype, compared to the A33 phage-cured strain (Table 2 ), thus highlighting that in S. thermophilus , likewise in L. lactis , the cell wall integrity is correlated with biofilm formation. More recently, S. thermophilus biofilm formation was correlated to the presence of the cell-wall protease PrtS which was demonstrated to trigger an aggregative phenotype ( Bassi et al, 2017 ), but this cannot be the case of strain DSM20617 T because it is protease-negative ( Arioli et al, 2007 ). In addition, to investigate the role of phage lysin in the S. thermophilus chain length, we evaluated the differential sedimentation rates of bacteria according to their chain-forming ability and/or cell size in semi-liquid medium (i.e., liquid M17 – lactose medium containing 0.15% wt/vol agarose).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some strains can form biofilms on stainless steel. These can cause many problems in cheese manufacturing plants such as undesirable contamination of dairy products and uncontrolled milk acidification during food production (Bassi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining attached cells were marked with 0.3% crystal violet. We removed the excess crystal violet solution by washing with bi-distilled water; the attached cells were resuspended with a 10% acetic acid solution and quantified by a spectrophotometric measurement at 590 nm, as described by Bassi et al (2017) with some modifications. To assess whether these strains showed significant differences in their ability to form biofilms (crystal violet staining method), 12 inoculation replicates were made, and an ANOVA was carried out with Tukey's honestly significant difference test.…”
Section: Biofilm Formation Assaymentioning
confidence: 99%